2013
DOI: 10.1002/ana.23894
|View full text |Cite
|
Sign up to set email alerts
|

G51D α‐synuclein mutation causes a novel Parkinsonian–pyramidal syndrome

Abstract: We have identified a novel SNCA G51D mutation that causes a form of PD with unusual clinical, neuropathological, and biochemical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
499
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(510 citation statements)
references
References 34 publications
(65 reference statements)
4
499
2
5
Order By: Relevance
“…Both immunohistochemical (17,22) and proteomic studies (20) have shown that α-Syn within LBs and other different inclusions can be ubiquitinated and phosphorylated at S129 and/or at Y125 (17,22,30,31). Interestingly, exogenously prepared α-Syn fibrils are rapidly ubiquitinated and phosphorylated at S129 upon internalization in mammalian cell lines and following stereotaxic injection and uptake by neurons in mouse brain (32,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both immunohistochemical (17,22) and proteomic studies (20) have shown that α-Syn within LBs and other different inclusions can be ubiquitinated and phosphorylated at S129 and/or at Y125 (17,22,30,31). Interestingly, exogenously prepared α-Syn fibrils are rapidly ubiquitinated and phosphorylated at S129 upon internalization in mammalian cell lines and following stereotaxic injection and uptake by neurons in mouse brain (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Despite several reports demonstrating that ubiquitinated α-Syn is also phosphorylated at its C terminus (S129 and Y125) (17,22,30,31), the interplay across these modifications has not previously been investigated. Our results demonstrate that the effect of phosphorylation at Y125 on α-Syn aggregation is dependent on the length of the poly-Ub chain.…”
Section: Discussionmentioning
confidence: 99%
“…Mis‐sense mutations13, 36, 37, 38, 39, 40 and duplications or triplications of the SNCA gene, which encodes αS, lead to autosomal dominant early onset PD 41, 42. It has previously been shown that the formation of αS oligomers in vitro is concentration dependent,12 and ADPAINT now enables us to determine whether this dependence is reflected in cellular models that overexpress αS.…”
mentioning
confidence: 99%
“…Therefore, the identification and validation of biomarkers of PD is crucial for early diagnosis, monitoring the progression of the disease, designing clinical trials, and assessing the effectiveness of therapeutic strategies. The presence of fibrillar and aggregated forms of ␣-syn within LBs combined with the findings that genetic mutations (3)(4)(5)(6)(7) or gene duplication or triplication (8,9) promote ␣-syn aggregation and fibrillization and cause early-onset forms of PD suggest that the process of LB formation plays a central role in neurodegeneration and the pathogenesis of PD. The molecular factors that contribute to triggering ␣-syn aggregation and LB formation remain unknown.…”
mentioning
confidence: 99%
“…This approach was implemented by our group in a recent study aimed at detecting the presence of truncated forms of ␣-syn and their phosphorylated counterparts in brain extracts of a mouse model overexpressing human A30P, which shows accumulation of pS129 ␣-syn similar to that observed in human synucleinopathy patients. 3 In this study, recombinant truncated forms of ␣-syn at Y133 and D135 were used (i) to optimize the conditions for detecting the corresponding C-terminal peptides in mouse model brain extract samples, (ii) to test the specificity of newly developed antibodies targeting the alternative C termini, and (iii) to compare the propensity of the truncated forms to be phosphorylated at S129 by PLK-3 relative to the full-length protein.…”
mentioning
confidence: 99%